Effect of coating method on the structure and properties of a novel PbO2 anode for electrochemical oxidation of Amaranth dye. (February 2019) - Elaissaoui, Ines; Akrout, Hanene; Grassini, Sabrina; Fulginiti, Daniele; Bousselmi, Latifa
Abstract: This study deals with the electrochemical degradation of Amaranth in aqueous solution by means of stainless steel (SS) electrodes coated with a SiOx interlayer deposited by Plasma Enhanced Chemical Vapour Deposition and a modified PbO2 top layer deposited by continuous galvanostatic electrodeposition. The morphological characterization of the PbO2 top-layer performed by Field Emission Scanning Electron Microscope put in evidence that the SiOx, interlayer allows obtaining a more integrated PbO2 /SS electrode with a very homogeneous PbO2 film. The composition of the lead oxide layer was investigated by X-ray Diffractometry, showing that the β-PbO2 /α-PbO2 ratio in the top layer deposited on the SiOx film was four times higher respect to the one deposited directly on the stainless steel surface. In addition, the electrochemical behaviour of SS/SiOx /PbO2 interfaces was studied by electrochemical impedance spectroscopy (EIS). The EIS results showed that the presence of SiOx favors electron transfer within the oxide layer which improves electro-oxidation capability. Moreover, bulk electrolysis showed that over 100% colour removal and 84% COD removal, using SS/SiOx /PbO2 at acidic pH were reached after 300 min. High Performance Liquid Chromatography analysis was used for the quantitative determinations of initial Amaranth dye molecule removal and to evaluate its specific degradation rate. In order to evaluate the phototoxicity of treated solution with different by-products, different tests of germination were performed and proved that the electrochemical treatment with modified PbO2 could be as an efficient technology for reducing hazardous wastewater toxicity and able to produce water available for reuse. Graphical abstract: Highlights: A novel modified PbO2 electrode was prepared. The electro-deposition method can enhance the stability of lead oxide film. The adding of SiOx interlayer to PbO2 anode is used to modify PbO2 electrode. Electrochemical method is proved to be a useful way of degrading Amaranth dye.